2018
DOI: 10.1017/hpl.2018.4
|View full text |Cite
|
Sign up to set email alerts
|

Target alignment in the Shen-Guang II Upgrade laser facility

Abstract: The Shen-Guang II Upgrade (SG-II-U) laser facility consists of eight high-power nanosecond laser beams and one short-pulse picosecond petawatt laser. It is designed for the study of inertial confinement fusion (ICF), especially for conducting fast ignition (FI) research in China and other basic science experiments. To perform FI successfully with hohlraum targets containing a golden cone, the long-pulse beam and cylindrical hohlraum as well as the short-pulse beam and cone target alignment must satisfy tight s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
8
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 21 publications
0
8
0
Order By: Relevance
“…The Shen-Guang II Upgrade (SG-II-UP) facility has eight laser beams of total energy 24 kJ and duration 3 ns at the third harmonic (351 nm) for implosion, coupled to a petawatt beamline delivering 1 kJ energy in 1 ps at the first harmonic (1053 nm) for the generation of a relativistic electron beam [103] . Studies of EMP generation in this facility by using nanosecond beams have been reported in Refs.…”
Section: Emp Experiments On Shen-guang III (Lfrc) Andmentioning
confidence: 99%
“…The Shen-Guang II Upgrade (SG-II-UP) facility has eight laser beams of total energy 24 kJ and duration 3 ns at the third harmonic (351 nm) for implosion, coupled to a petawatt beamline delivering 1 kJ energy in 1 ps at the first harmonic (1053 nm) for the generation of a relativistic electron beam [103] . Studies of EMP generation in this facility by using nanosecond beams have been reported in Refs.…”
Section: Emp Experiments On Shen-guang III (Lfrc) Andmentioning
confidence: 99%
“…This is less than the required (RMS) for the detailed description of the target alignment system (see Ref. [83]).…”
Section: Performance Of the Sg-ii Up Facilitymentioning
confidence: 97%
“…The target production area includes high-precision technologies for target fabrication, injection and tracking. These technologies are currently an important research stage in the leading laboratories of the world [9][10][11][12][13][14][15][16][17][18]. Target compression and ignition is regarded as a major challenge to the IFE community.…”
Section: Introductionmentioning
confidence: 99%